Monitoring of a football team during a competition season by measuring serum myosin isoforms - Cusso, R.; Carmona, G.; Cadefau, J. A.; Solanas, J. L.; Revuelta, G.; Maestro, A.; Guerrero, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: We developed an ELISA methodology sandwich type to improve the medical diagnosis of the professional sports men muscle damage. The new technic was applied to obtain basal values of a reference population and to monitor a team players during a football season. Methods: 49 reference volunteer and 27 male professional football players from the Sporting of Gijon Club participated in this study. In the case of players, blood was obtained at the pre-season and at different time-points along the season. In ELISA test monoclonal anti myosin fast and slow antibodies tapissed a polystyrene plate. The calibration curve was performed with purified pork myosin. To close the sandwich ELISA, the polyclonal rabbit antibody was added. Plates were incubated with an anti-anti rabbit antibody linked to peroxidase and TMB substrate for the luminescent reaction of the peroxidase. The absorbance was read at 450 nM wavelength. Results: The calibration curve shows a very good linearity. The intra-assay coefficient of variation was assayed using three different samples low, medium and high values. CV is below 11% for Fast myosin and below 6% for Slow myosin. Linearity for Fast myosin was 80% and for the Slow myosin 90%. Comparing the results of the football team with reference population we observe that our players move below the normal average respect to Fast myosin and above the normal average respect to Slow myosin. In the competitive preseason there is not increase in serum but at the beginning of season both types of fiber are damaged but not in the same magnitude, as the ratio indicated, due to the tactic and training conducted by the team. Discussion: The new ELISA assay has greater speed, sensitivity and reproducibility that the Western Blot and shorten the result time from 48 to 4 hours, allows for processing 26 samples at the same time and it is more economic. Values for Fast myosin in the reference population shows no differences between sex and age. Significant differences were found of Slow myosin from older group (45-66) compared to younger (20-44). It may be caused by their lifestyle, which must be more sedentary at maturity, or loss of muscle into mature persons. Moreover, tracking myosin isoforms during a season of racing in a soccer team offers new insight into the state of the fast and slow fibers relating it to the possible significance of sarcomere damage that can occur during different phases of training and competition.